2018
DOI: 10.1021/acs.organomet.7b00824
|View full text |Cite
|
Sign up to set email alerts
|

Considering a Possible Role for [H-Fe4N(CO)12]2– in Selective Electrocatalytic CO2 Reduction to Formate by [Fe4N(CO)12]

Abstract: Fe 4 N(CO) 12 ] − is a first-row transition element electrocatalyst that selectively produces C−H bonds to give formate from CO 2 in water at −1.2 V vs SCE. We present a thermochemical analysis which probes the possibility that [H-Fe 4 N(CO) 12 ] 2− ((H-1) 2− ) is an intermediate in this process: we show that (H-1) 2− is accessible at −1.2 V vs SCE, but if it were formed, we predict that it would generate H 2 .[Fe 4 N(CO) 12 ] 3− and (H-1) 2− were interrogated spectroscopically, and the product of CO loss, [Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
1
15
0
1
Order By: Relevance
“… 47 The dissociation pathway was found using high temperature ab initio molecular dynamics and relaxed to the minimum energy path to calculate the activation barrier. 48 The calculations predict a structure of 2 3– in remarkable agreement with the X-ray crystal structure that was determined concurrently, 17 lending further confidence to the level of theory used in this study. We also compare the CO dissociation barrier height to the analogous reaction after only one reduction event: 1 2– → 2 2– + CO, and show that dissociation from this electronic state is energetically uphill, though the activation free energy of CO dissociation is similar in both states.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“… 47 The dissociation pathway was found using high temperature ab initio molecular dynamics and relaxed to the minimum energy path to calculate the activation barrier. 48 The calculations predict a structure of 2 3– in remarkable agreement with the X-ray crystal structure that was determined concurrently, 17 lending further confidence to the level of theory used in this study. We also compare the CO dissociation barrier height to the analogous reaction after only one reduction event: 1 2– → 2 2– + CO, and show that dissociation from this electronic state is energetically uphill, though the activation free energy of CO dissociation is similar in both states.…”
Section: Introductionsupporting
confidence: 77%
“…In an accompanying experimental work, the X-ray crystal structure of 2 3– is reported. 17 Simulations that uncover the mechanisms of side reactions are important to the overall strategy for designing molecular catalysts which are resistant to them. In this respect, this article describes the redox properties and CO dissociation pathway of this complex using computational quantum chemistry to complement the experimental findings and provide atomic-resolution insights.…”
Section: Introductionmentioning
confidence: 99%
“…A nonelectrochemical control experiment revealed that (H-1) − is the active form and not (1 − ). In a more recent follow-up study, Taheri et al [63] investigated the possible alternatives to the ECCE scheme proposed in Figure 26. Therefore, as an attempt to improve the hydricity, an analogous [H-Fe 4 N(CO) 12 ] 2− (H-1) 2− was synthesized.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…To achieve this, the authors designed a control experiment where the number of pendant proton donors are varied in a series of Co-aminopyridine complexes. [63] Copyright 2018, American Chemical Society. Finally based on this Adv.…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
“…Berben reported solvent‐dependent product selectivity for electrocatalytic reduction of CO 2 using the iron cluster [Fe 4 (N)(CO) 12 ] − : high selectivity for formate (96 %) was observed in water, while H 2 was the major product in acetonitrile . Mechanistic studies identified a parallel between the product selectivity and hydricity of [HFe 4 (N)(CO) 12 ] − , a key catalytic intermediate . Hydride transfer from [HFe 4 (N)(CO) 12 ] − to CO 2 is exergonic (−9 kcal mol −1 ) in water, but endergonic (+5 kcal mol −1 ) in acetonitrile (Figure ).…”
Section: Hydride Transfer To Co2mentioning
confidence: 99%